If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 2.6 = 6.8x Reorder the terms: 2.6 + 12x = 6.8x Solving 2.6 + 12x = 6.8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6.8x' to each side of the equation. 2.6 + 12x + -6.8x = 6.8x + -6.8x Combine like terms: 12x + -6.8x = 5.2x 2.6 + 5.2x = 6.8x + -6.8x Combine like terms: 6.8x + -6.8x = 0.0 2.6 + 5.2x = 0.0 Add '-2.6' to each side of the equation. 2.6 + -2.6 + 5.2x = 0.0 + -2.6 Combine like terms: 2.6 + -2.6 = 0.0 0.0 + 5.2x = 0.0 + -2.6 5.2x = 0.0 + -2.6 Combine like terms: 0.0 + -2.6 = -2.6 5.2x = -2.6 Divide each side by '5.2'. x = -0.5 Simplifying x = -0.5
| 54=3y+x | | 54=3x+y | | 2(x+9)=30+18 | | (19+3)2=x | | 5/4k=5 | | 54-3(45)= | | 5-2(4x-2)+2x= | | xa+5=7x+b | | -9(x+4)+2x+5=6x+11 | | Y=3*X+2 | | 3(45)+x+6(45)+4x=180 | | 4xy+5xy-3xz-2xy+xy+3xz= | | 8x+6-9x=2-y-15 | | 8-10p+4+8p= | | z(3+2i)=iz+2 | | 2(x+5)+5=2x+9 | | 3x-250=2858 | | 2x+15=385/(x+1) | | 3x+54-3x+6x+4(54-3x)= | | (x+3)(x^2+2x+6)=0 | | 1/16x-3/4y=-1 | | 5b-3/3b-4b+1/5b | | .2y+.5x=4.05 | | 2/3n=-18 | | -12=.5x+x | | 3y+x=54 | | 2(x+8)=30+18 | | 3x+y=54 | | 4x+4x=50 | | -12=6+1y | | A=5H(b+B) | | 3(2x+8)=30+18 |